Attitudes of students towards the use of video-based media in physical education - Anne-Christin Roth; Maik Beege (Bern Open Publishing, 2024)
Introduction The importance of teachers' attitudes regarding the use of technology and media in schools and classrooms gains more recognition in the development of their professional competence. However, students often still hold limited views about digital media in educational settings. This limited perspective is likely due to the significant increase in media usage over the past two decades. It's assumed that students also desire to use media for learning purposes, which is particularly questionable in the subject of physical education, where physical activity is of central importance. Therefore, understanding students' attitudes toward media use, both inside and outside of school, is crucial, and it's a focal point of media educational efforts. To comprehensively study this, the social-psychological construct of attitude, with its cognitive, affective, and behavioral components, is considered (Zimbardo & Gerrig, 1996). Key questions revolve around characterizing student attitudes toward media use in physical education, identifying relationships between attitude components, and determining external factors that can promote positive attitudes. Methods Following the Technology Acceptance Model (Park, 2009), a questionnaire was developed to assess attitudes and validated through a survey of eighth-grade students (N = 202). External variables, cognitive attitude, affective attitude, and behavioral attitude dimensions were examined as separate aspects. These dimensions were refined and validated through reliability analysis and factor analyses. Using these validated scales and collected data, a structural equation model was created to illustrate the relationships between external factors and attitudinal dimensions. Results The proposed model demonstrated satisfactory fit to the data (RMSEA = .06; χ2/df ratio = 1.72; CFI = 0.90). The findings indicate that the use of media in physical education and the related self-efficacy in using media have a positive impact on the cognitive aspect of attitude. However, the cognitive component of attitude does not directly influence the intention to use media in physical education. Instead, positive evaluations of media use mediate the relationship between the cognitive component and the intention to use media. The intention to use media in physical education is primarily increased through positive affective evaluations. Conclusion A negative attitude toward using media in physical education can be attributed to a lack of access and insufficient self-efficacy in utilizing it. Therefore, interventions at both the student and teacher levels should focus on effectively introducing the benefits of media-supported physical education, with the goal of enhancing self-efficacy and reducing negative attitudes. This model will be further validated at the teacher level in subsequent studies to identify external factors suitable for targeted interventions. References Park, S. Y. (2009). An analysis of the Technology Acceptance Model in understanding university Students' behavioral intention to use e-learning. Educational Technology & Society, 12(3), 150-162. Zimbardo, P. G., & Gerrig, R. J. (1996). Psychologie. (7th transl. and rev. ed.). Springer.